The socio-economic characterization of the student’s career at the university of Guayaquil leveling - Borja Santillán, Maritza; Manola Zeballos, Johanna; Vásquez Portugal, Roxana (Revista Universidad de Guayaquil, 2018)
The present article seeks to promote the use of a tool that allows the students of Leveling of the University of Guayaquil to be characterized from the socioeconomic level. The Technical Direction of Career Leveling requires knowing how high school graduates enter this new student stage. To this end, an instrument has been established since the beginning of the school period to gather the information and data necessary to characterize the student body. The instrument, established as a pedagogical tool within the action of the Career Leveling, pursues as objective to know the reality that lives the student, because when knowing it the institution is in a better position to help it to have an optimal cognitive development, both during the learning process as outside the classroom. Hence, the objective of promoting the use of a tool capable of carrying out a deep socioeconomic characterization of the student of Career Leveling at the University of Guayaquil.